A World Challenged : Fighting Terrorism in the Twenty-First Century - Primakov, E. M. (Evgeniĭ Maksimovich) (Book collections on Project MUSE., 2004)
"In this account, former Russian premier Yevgeny M. Primakov considers the threats posed by independent terrorist organizations to the security of the global community." "As the attacks of September 11, 2001, made clear, the course of international affairs is no longer shaped exclusively by cooperation and confrontation among nations. Stateless factions with extreme agendas - their methods enhanced by globalization and technological advances - pose serous threats to global stability." "Primakov expresses grave concern over the likelihood that independent terrorist organizations will obtain weapons of mass destruction. More than 100 nations are stockpiling nuclear material, he writes, and there is no reason to believe that all of it is well managed or protected. A terrorist group intent on developing a weapon can easily find the information and fissile material to develop a compact nuclear device." "He recommends that the global community develop a comprehensive Charter on Terrorism to facilitate criminal prosecution of terrorism. And he urges Russia and the United States to join forces more readily to share information and intelligence about emerging terrorist threats."--Jacket